Changes in Type 2 Diabetes Medication Utilization and Costs in the United States, 2014–2019. Issue 9 (29th September 2021) - Neilson, Lynn M.; Munshi, Kiraat D.; Peasah, Samuel K.; Huang, Yan; Swart, Elizabeth C.S.; Henderson, Rochelle; Manolis, Chronis; Good, Chester B.
Abstract : Objective: The objective of this study was to describe national changes in utilization and associated costs of antidiabetic medications in the United States from 2014 to 2019, across different drug classes and insurance plans. Research Design and Methods: This retrospective, cross-sectional study examined administrative claims from a large national pharmacy benefits manager from January 1, 2014, to December 31, 2019. Patients aged 18 years and above enrolled in commercial, Medicare, or Medicaid health plans who filled ≥1 prescription claim for an antidiabetic medication(s) during the 6-year period were included. Utilization was examined as the total number of 30-day adjusted prescription fills per user per month (PUPM). Gross costs were calculated as the sum of plan costs (net of rebates) and member out-of-pocket costs. Differences in mean utilization and costs PUPM between 2014 and 2019 for each medication class were calculated. Results: The final analytic sample increased from 745, 290 patients in 2014 to 1, 596, 006 in 2019. Antidiabetic medication utilization increased by 8.8% from 2014 to 2019, driven by increases in sodium-glucose cotransporter 2 inhibitor (48.7%; P <0.001), glucagon-like peptide 1 receptor agonist (11.8%; P <0.001), insulin (8.1%; P <0.001), and metformin (2.9%; P <0.05) utilization. Average costs PUPM rose 47.5% ( P <0.001), from $126.52 in 2014 to $186.58 in 2019. Sodium-glucose cotransporter 2 inhibitors, glucagon-like peptide 1 receptor agonists, and combination drugs contributed significantly to these increased costs, with 6-year cost differences of 57.3%, 46.9%, and 47.2%, respectively (all P <0.001). Conclusion: Our study demonstrates a shift in antidiabetic medication class utilization from 2014 to 2019, where associated costs net of rebates significantly increased to a disproportionately greater extent than the significant increase in utilization PUPM.